Enhancement of thermal and mechanical stabilities of silicon doped titanium nitride coating by manipulation of sputtering conditions - Mohammadpour, Ehsan; Yun, Willey Hsien Liew; Mondinos, Nicholas; Altarawneh, Mohammednoor; Lee, Sunghwan; Radevski, Nik; Minakshi, Manickam; Amri, Amun; Lim, Hong Ngee; Jiang, Zhong Tao (Elsevier, 2022)
This study investigates the influence of substrate (AISI M42 tool steel) bias voltage (from −30 to −80 V), on the mechanical properties of magnetron sputtered TiSiN coating derived from Ti and Si targets. Thermal stability, microstructure (crystallite size, microstrain, lattice constant), morphology and mechanical (hardness, Young's modulus, residual stresses) properties, of the deposited TiSiN coatings, were investigated with synchrotron powered X-ray diffraction (SR-XRD), X-ray photoelectron spectroscopy, field emission scanning electron microscopy, and nanoindentation techniques. Rietveld analysis, of the in-situ SR-XRD, in the temperature range of 25–800 °C, demonstrated cubic TiN form in (Ti,Si)N solid solutions, with TiO2 and Ti2O3 identified at lower bias voltages. Density functional theory supplemented the experimental results. Increase in the bias voltage resulted in: (i) a decrease in Si content, (ii) significant smoothening of surface morphology, (iii) change in the phase composition and microstructure, (iv) improved oxidation resistance and thermal oxidation threshold, and (v) hardness and Young's modulus of the coatings increased up to 50% to 33 GPa and 450 GPa, respectively.